The Plant Cell Wall: A Dynamic Barrier Against Pathogen Invasion - Underwood, William (Frontiers in Plant Science, 2012)
Prospective plant pathogens must overcome the physical barrier presented by the plant cell wall. In addition to being a preformed, passive barrier limiting access of pathogens to plant cells, the cell wall is actively remodeled and reinforced specifically at discrete sites of interaction with potentially pathogenic microbes. Active reinforcement of the cell wall through the deposition of call wall appositions, referred to as papillae, is an early response to perception of numerous categories of pathogens including fungi and bacteria. Rapid deposition of papillae is generally correlated with resistance to fungal pathogens that attempt to penetrate plant cell walls for the establishment of feeding structures. Despite the ubiquity and apparent importance of this early defense response, relatively little is known about the underlying molecular mechanisms and cellular processes involved in the targeting and assembly of papillae. This review summarizes recent advances in our understanding of call wall-associated defenses induced by pathogen perception as well as the impact of changes in cell wall polymers on interactions with pathogens and highlights significant unanswered questions driving future research in the area.